Effectiveness and cost-effectiveness of interventions to increase knowledge and awareness of attention deficit hyperactivity disorder: a systematic review. - McKenna, Kaitlyn; Wanni Arachchige Dona, Sithara; Gold, Lisa; Silk, Tim J.; Le, Ha N. D. (European Child & Adolescent Psychiatry, 2025)
Various interventions, including caregiver education, psychoeducation, teacher and clinician training and behavioral management embedded with education, are available to enhance awareness and knowledge among caregivers, teachers, and clinicians. This review synthesizes evidence on the effectiveness and cost-effectiveness of interventions to increase ADHD awareness and knowledge for caregivers, clinicians, and teachers. Peer-reviewed literature was identified through the systematic searches of six databases: MEDLINE Complete, APA PsycInfo, CINAHL Complete, ERIC, Global Health and EconLit. Two independent reviewers completed a two-stage screening process and quality assessment. Results are presented as a narrative synthesis. Economic evaluation study cost data were converted for comparability. Of the 5963 results, 28 studies were included. Most interventions were found to be effective in increasing the awareness and knowledge of ADHD among caregivers, clinicians, and teachers. Clinician knowledge and capacity to assess, diagnose and treat ADHD were improved. Of the economic evaluation studies, interventions were promising in parent education, and behavioral management and psychosocial therapy interventions were found to be cost-effective. The review provides important insights about effective and cost-effective interventions to increase ADHD awareness and knowledge. These insights are critical to effectively plan services/interventions for families and children with ADHD. Further research in economic evaluation of interventions is needed to assist policy-decision making.